Fish Assemblage Subjected to Strong Anthropogenic Stress: The Case of the Barra Bonita Reservoir, Tietê River Basin, São Paulo, Brazil - Petesse, M. L. [UNESP] (My University, 2016)
The Barra Bonita reservoir (S=310 km2; z̄ =10,1 m) is an ecosystem subjected to strong anthropogenic stress. It is located in the central part of the Tietê river basin - São Paulo State, characterized by the widespread urbanization, industrial development and intensive agricultural use of the soil. The Barra Bonita reservoir has high social-economic importance due to hydropower generation, navigation and fisheries. From a limnological point of view, it is classified as polymictic and eutrophic. The purpose of this study was to characterize the actual fish assemblage in the reservoir and, by means of the species-abundance relationship, value its organization in relation to the disturbances caused by the anthropogenic impact. For the fish sampling we chose 24 sites located in three different habitats: reservoir shoreline, mouth of tributary and centre. Samples were taken in two periods of the year: dry season (winter, August-September 2003), and rainy season (summer-February 2004). Fish sampling was standardized by using 10 gillnets with mesh sizes ranging from 3 to 12 cm between opposite knots and funnel traps. At each point we also measured some morphological, physical-chemical and environmental variables. Multivariate analyses (three way-anova and ancova) were employed to, respectively, point out space and temporal variations in the Catch per Unit Effort in weight (CPUEW) and to detect the importance of morphological, physicalchemical and environmental variables on Shannon species diversity (H’ in number and weight). A total of 35 species, belonging to 14 families and 4 orders, were caught. Fish assemblage is composed of small body-sized species, with wide feed flexibility and high reproductive compensation. The superposition of the biological cycles of the fishes with the hydrological management of the reservoir, suggests that only those with multiple spawn and/or parental care have success. The CPUEW distribution shows significant statistical differences between seasons, zones and habitat, indicating the presence of transversal migration from the centre to the shoreline and mouth of the tributary habitats, especially in the rainy season. The variables that influenced the diversity of the fish assemblage were: depth, transparency and landscape for H’N and H’W; temperature (H’N); conductibility and macrophytes (H’W). The correlation of diversity with the depth was negative, showing that the tributary mouths and the shoreline habitats of the reservoir are the most explored by the ichthyofauna. The environmental variables selected (surrounding landscape and macrophytes beds) act respectively as external feeding support and shelter/nursery habitat, revealing the essential importance of the structural environmental complexity for the diversity maintenance in reservoirs.